Ascospore discharge, germination and culture of fungal partners of tropical lichens, including the use of a novel culture technique - E. Sangvichien; D.L. Hawksworth; A.J.S. Whalley (IMA Fungus)
A total of 292 lichen samples, representing over 200 species and at least 65 genera and 26 families, were collected, mainly in Thailand; 170 of the specimens discharged ascospores in the laboratory. Generally, crustose lichens exhibited the highest discharge rates and percentage germination. In contrast, foliose lichen samples, although having a high discharge rate, had a lower percentage germination than crustose species tested. A correlation with season was indicated for a number of species. Continued development of germinated ascospores into recognizable colonies in pure culture was followed for a selection of species. The most successful medium tried was 2 % Malt-Yeast extract agar (MYA), and under static conditions using a liquid culture medium, a sponge proved to be the best of several physical carriers tested; this novel method has considerable potential for experimental work with lichen mycobionts.